Effects of Pin Diameter and Welding Position of Micro Friction Stir Spot Welding to the Mechanical Properties on Longitudinal Square Honeycomb Corrugated Panels - Sunar Baskoro, Ario; Mustaqim, Abdi; Azwar Amat, Muhammad; Muzakki, Hakam (International Journal of Engineering and Technology, 2018)
Weld aluminum material especially on thin plate is difficult because it cannot withstand the heat due to welding. Friction stir spot welding which is a solid state welding can overcome this damage because it does not require high temperatures. Then this technology is applied to the manufacture of lightweight structures square longitudinally corrugated honeycomb core sandwich panel product. This study is to determine how the pin diameter and welding position at straight and zig-zag position to the strength of the product. From the results, it is shown that diameter of the pin directly proportional to the strength of shear load. And in bending test, weld spot is an area that is weaker than the other area.Â Â